Amphiphilic Janus Gold Nanoparticles Prepared by Interface‐Directed Self‐Assembly: Synthesis and Self‐Assembly. Issue 9 (8th July 2014) - Liu, Guannan; Tian, Jia; Zhang, Xu; Zhao, Hanying
Abstract Materials with Janus structures are attractive for wide applications in materials science. Although extensive efforts in the synthesis of Janus particles have been reported, the synthesis of sub‐10 nm Janus nanoparticles is still challenging. Herein, the synthesis of Janus gold nanoparticles (AuNPs) based on interface‐directed self‐assembly is reported. Polystyrene (PS) colloidal particles with AuNPs on the surface were prepared by interface‐directed self‐assembly, and the colloidal particles were used as templates for the synthesis of Janus AuNPs. To prepare colloidal particles, thiol‐terminated polystyrene (PS‐SH) was dissolved in toluene and citrate‐stabilized AuNPs were dispersed in aqueous solution. Upon mixing the two solutions, PS‐SH chains were grafted to the surface of AuNPs and amphiphilic AuNPs were formed at the liquid–liquid interface. PS colloidal particles decorated with AuNPs on the surfaces were prepared by adding the emulsion to excess methanol. On the surface, AuNPs were partially embedded in the colloidal particles. The outer regions of the AuNPs were exposed to the solution and were functionalized through the grafting of atom‐transfer radical polymerization (ATRP) initiator. Poly[2‐(dimethamino)ethyl methacrylate] (PDMAEMA) on AuNPs were prepared by surface‐initiated ATRP. After centrifugation and dissolving the colloidal particles in tetrahydrofuran (THF), Janus AuNPs with PS and PDMAEMA on two hemispheres were obtained. In acidic pH, Janus AuNPs are amphiphilic and are able to emulsify oil droplets in water; in basic pH, the Janus AuNPs are hydrophobic. In mixtures of THF/methanol at a volume ratio of 1:5, the Janus AuNPs self‐assemble into bilayer structures with collapsed PS in the interiors and solvated PDMAEMA at the exteriors of the structures.